House Yard as a Productive Landscape during the Covid-19 Pandemic in Metro Municipality, Lampung Province - Aisyah Nur Fadila; Hadi Susilo Arifin; Nurhayati Nurhayati; Aris Munandar (Institut Pertanian Bogor, 2025)
This house yard (pekarangan) research was conducted at three sites of the Way Seputih-Sekampung watershed, which are represented by the upstream (Mulyosari Village), middle (Margodadi Village), and downstream (Tejosari Village), Metro Municipality, Lampung Province from May to July 2022. The objective of this research is to analyze the yard as a productive landscape by analyzing: 1) plant composition, 2) the diversity of plant species, and 3) utilization of the yard. Surveys and questionnaires were used. The number of yards was determined by purposive sampling, totaling 30 yards belonging to members of the Women Farmers’ Group (KWT) at each location. The results showed that horizontal diversity includes ornamental, fruit, vegetable, medicinal, and starch-producing plants. Sixteen types of plants were frequently found in 46% of yards. It was found that the Shannon-Wiener species diversity decreased from upstream to downstream, that is, upstream (2.41), middle (2.33), and downstream (1.82). Although the diversity of plant species is moderate on average, communities use their yards according to their function. The community was aware of the benefits of the yard, particularly its contribution to environmental sustainability, as indicated by the assessment index for the upstream (87%), midstream (93%), and downstream (94%) sites. Thus, the yard is very useful for the community as a place for interaction during the Covid-19 pandemic. Such benefits are said to be better if landscape management is carried out in a planned and environmentally friendly manner. Keywords: community, home garden utilization, landscape management, pandemic, species diversity